(untitled) - Reid, R. Dan (New York, 2002)
Features the latest concepts and applications while preserving the core concepts that have made the text a market leader. Careful explanations and approachable format supports students in understanding the important operations management concepts as well as applying tools and methods. By providing detailed examples, solved problems, questions, and cases students learn by doing, and continues to offer more support for 'doing Operations' than any other
Keywords: Production management